Analisis Citraan dalam Kumpulan Cerpen Cinta yang Tak Terucap: Dan Sehimpun Cerita Tentangnya Karya Saad Pamungkas dkk. - Sri Rahayu; Alintang Raya Milaniza; Delvi Witri Haryani; Eva Debora Lumban Tobing; Haura Hafizhah; Meitia Haspita Rani; Olivia; Saidatina Ardiani; Siti Aisyah; Zilfa Zaldiah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to describe the use of imagery in the short story collection Cinta yang Tak Terucap: Dan Sehimpun Cerita Tentangnya by Saad Pamungkas dkk. This study is motivated by the importance of studying imagery in literary works because imagery can help readers build imagination and understand the atmosphere, events, and experiences of characters in the story. This study uses a descriptive method with a qualitative approach. The source of research data is the short story collection Cinta yang Tak Terucap: Dan Sehimpun Cerita Tentangnya by Saad Pamungkas dkk. Data collection was carried out using hermeneutic techniques through reading, recording, and concluding techniques. Data analysis was carried out through the stages of identification, classification, description, analysis, and interpretation of data based on the type of imagery. This study focuses on the analysis of twenty data representing four types of imagery, namely visual, auditory, tactile, and motion imagery. The results of the study show that the author utilizes various types of imagery to strengthen the depiction of characters, atmosphere, and events in the story. Visual imagery is used to present vivid visuals, auditory imagery is used to enliven the atmosphere through sound and dialogue, tactile imagery is used to describe the characters’ tactile experiences, and motion imagery is used to show activities that bring the story to life. The use of these imageries makes the story more engaging and helps readers better understand and visualize the story’s content.